Solar retrofitting in social housing: a case study in Savona - Andrea Giachetta (Techne, 2012)
In relation to the social Housing’s theme, sustainable requalification interventions on the building heritage in the urban fringes dating back to the WWII postwar play an important role as those are characterized by buildings which offer poor energy performances. These interventions are potentially very effective, although at the same time they raise implementation and management issues, with which it is fundamental to confront, with a view to pursue serious housing and social policies. With this object in view, the introduction of a recently completed intervention in a social housing borough in Savona, also through the use of passive solar systems, offers suggestions and hints for reflection, due to the repeatibility of some adopted solutions and design principles.